Public Libraries and the Opioid Crisis, Part 1: Context and Commitment - Real, Brian; Bogel, Gayle (Public Library Quarterly, 2019)
Public libraries have been significantly affected by the opioid crisis. The fact that patrons can enter libraries freely and do not need a reason to be there has resulted in overdoses occurring in many such buildings throughout the country. In response to this, library directors have developed plans of action that, in some cases, include training librarians to administer the opioid overdose reversal drug Naloxone. This present article – the first in a two-part study – is based on interviews with representatives from libraries that have been significantly affected by the opioid crisis. After describing these community circumstances, the authors analyze various ways that each library has prepared to respond to overdoses and other emergency situations.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/172-972-683-218-803, pop00020 tex.type: [object Object]
Keywords: Narcan; Public libraries; dept.ils; opioid dependency; opioids; peer-reviewed